Developmental Origins of Health and Disease (DOHaD) From Biological Basis to Clinical Significance (Advances in Experimental Medicine and Biology,, 2018)
This book addresses the developmental origins of health and disease (DOHaD), a new medical concept that demonstrates that various adult diseases start in the fetal period. It discusses our current understanding of the molecular mechanisms of DOHaD, including gene body epigenetics and non-coding RNA, and comprehensively examines diseases such type 2 diabetes, a well known as standard DOHaD-associated disease, as well as non-alcoholic fatty liver disease, hypertension and neurodevelopmental disorders. It argues that most adult diseases start at a very early stage, such as in the fetal and neonatal periods, and that earlier prevention and intervention would result in better outcomes for adult diseases such as type 2 diabetes and cardiac disorders, which are increasing in both developed and developing countries. The book appeals to obstetricians and pediatricians, as well as physicians who treat adult patients, wanting to understand the origins of diseases.